131k views
4 votes
Subtract: 3x to the power 2 - 6x - 4 from 5 + x - 2xto the power 2.

1 Answer

4 votes

Answer:


-8x^2 - 4x + 29 \\

Explanation:

Second expression evaluates to:


(5 + x -2x)^2 = (5 -x)^2 = (-x+5)^2 = x^2 + 2(-x)(5) +5^2 = x^2 -10x + 25 (1)

For (1) We are using the rule
(a+b)^2 = a^2 +2ab + b^2\\\\

Here
a = -x, b = 5\\\\

First expression evaluates to


(3x)^2 -6x - 4 = 9x^2 -6x -4 (2)

Subtract (2) from (1)


x^2 - 10x +25 - (9x^2 -6x -4) = x^2-9x^2 -10x - (-6x) +25 -(-4)\\\\= -8x^2 - 4x + 29 \\

User Prakash Sharma
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.